Metallurgical failure analysis of non-separation of isolation pyro valve used in space applications. (August 2021) - Manwatkar, Sushant K.; Jalaja, K.; Dhanya, M.S.; Narayana Murty, S.V.S.; Sivakumar, D.; Pant, Bhanu; Mohan, M.
Highlights: During testing at 20 K, membrane separation was not observed in a pyro valve. Metallurgical analysis was conducted to address the non-separation. Plastic deformation was observed at the notch location due to strain hardening. Higher root radius at notch led to metal forming rather than severance. Importance of maintaining tolerances in critical applications is highlighted. Abstract: Isolation pyro valves fabricated from AISI 321 austenitic stainless steel are performance-critical components used in launch vehicle propulsion systems. These valves isolate the fuel and oxidizer separated by a thin membrane that will be severed during its operation. As a part of the qualification program, a set of pyro valves were tested at the operating temperature of 20 K. During post-test examination of the hardware, membrane separation was not observed in one of the pyro valves tested. The failed and successfully tested valves were analysed to understand the reason for the non-separation of the pyro valve membrane. The present work brings out the details of metallurgical and mechanical aspects of the failed as well as successfully tested isolation pyro valves.